Integrasi Strategic Management Accounting (SMA) dan Environmental, Social, and Governance (ESG) Metrics untuk Penyusunan Strategi Jangka Panjang: Kajian Literatur - Edito Biantara Titus; Ali Tafriji Biswan (Ekonomis: Journal of Economics and Business, 2026)
This study aims to develop a conceptual understanding of how ESG (Environmental, Social, and Governance) metrics can be integrated into SMA (Strategic Management Accounting) to support a company's long-term strategy. The method used is a systematic literature review of 20 scientific articles from 2017–2025 that discuss management accounting, sustainability accounting, ESG, and sustainability reporting. The results show that SMA–ESG integration has the potential to improve the quality of strategic information, strengthen accountability mechanisms, and support sustainability risk management, although its implementation still faces challenges related to internal standards, data quality, and organizational capabilities. This study offers a conceptual framework for SMA–ESG integration that can be used as a basis for empirical testing in companies in Indonesia.